Uniform solution for the flow past a slender body with an attached shock wave in radiative magnetogasdynamics - Singh L.P.; Ram S.D.; Singh D.B. (My University, 2025)
A systematic perturbation scheme is used to study the propagation of a weak shock wave attached to a slender body in a supersonic flow of plasma with thermal radiation and investigate as to how the coupling between the radiative transfer and magneto-hydrodynamic phenomena affects the flow field. The analytical solution of the flow field has been presented up to the second order of ε. The shape of the shock wave attached to the slender body of revolution is obtained, which however can be expressed explicitly in terms of known functions when the radiative decay length is of the same order as the typical body length. Also, the shock angle at the tip of the projectile is obtained. © 2010 Elsevier Ltd.